THE ROLE OF CLOUD COMPUTING TECHNOLOGY IN INCREASING WORK FLEXIBILITY IN THE HYBRID ERA - Witanti, Wina (MSJ : Majority Science Journal, 2025)
Digital transformation post-COVID-19 pandemic has accelerated the adoption of cloud computing technology to support hybrid work models that demand high flexibility, virtual collaboration, and cross-site employee mobility. This study aims to analyze the role of cloud computing technology in increasing work flexibility in the hybrid era through a Systematic Literature Review (SLR) approach to the latest studies for the 2020–2025 period. The results of the analysis show that cloud computing contributes significantly to increasing work flexibility through three main mechanisms, namely providing real-time data and application access, facilitating cross-site collaboration through AI-based platforms, and scalability and resource elasticity capabilities that support cost efficiency and rapid response to changing business needs. Cloud implementations have also been proven to accelerate decision-making, increase team productivity, and strengthen organizational cohesion in a hybrid work environment. On the other hand, challenges such as data security and privacy issues, reliance on internet connectivity, and the complexity of integration with legacy systems remain major obstacles. These findings confirm that cloud computing is not only a supporting technology, but also a strategic enabler for organizations to create an adaptive and sustainable hybrid work ecosystem. This study recommends the implementation of hybrid or multi-cloud architecture, strengthening network infrastructure, and developing human resource capacity so that organizations are able to maximize the potential of cloud computing optimally.